Increased pupil dilation to angry faces predicts interpersonal stress generation in offspring of depressed mothers. (2nd May 2017) - Feurer, Cope; Burkhouse, Katie L.; Siegle, Greg; Gibb, Brandon E.
Abstract : Background: Interpersonal stress generation is one mechanism hypothesized to increase risk for the intergenerational transmission of depression. Although there is some evidence of stress generation in offspring of depressed mothers, specific predictors of stress generation in these youth remain unknown. The goal of this study was to examine a peripheral measure of cognitive‐affective reactivity (i.e. pupil dilation) to emotional interpersonal stimuli as a predictor of stress generation in offspring of depressed mothers. Method: The study included 129 mothers and their offspring (ages 8–15) recruited from the community who participated at two time points separated by 6 months. Youth's average pupil dilation to emotional faces (angry, happy, sad) as well as maternal lifetime history of major depressive disorder were assessed at baseline. In addition, both time points included assessments of youth's levels of self‐generated (dependent) and independent episodic life stress in the preceding 6 months. Results: Youth's pupil dilation to angry, but not sad or happy, faces predicted prospective increases in dependent interpersonal stress across the follow‐up. This effect was only observed in offspring of depressed mothers and was not seen in offspring of never‐depressed mothers. Conclusions: This study highlights a potential risk factor (heightened reactivity to facial displays of anger) that may identify which offspring of depressed mothers are at greatest risk for interpersonal stress generation.